Kontruksi Etika Maduraisme Dalam Kode Etik Akuntan Profesional: Internalisasi Nilai “Gaik Bintang” Dalam Etika Profesi Akuntan - Mohamad Djasuli (Universitas Trunojoyo Madura, 2018)
This article has objectives to concots values of madurese culture’s local wisdoms in order to build the concept of accounting profession’s code of ethics in Indonesia holitically. The main foundation of the holistic accounting profession’s code of ethics in Indonesia is the local wisdoms in which are taken from the madurese culture from the madura folk song entitled “Ghai’ Bintang”. Ghai’ Bintang lyrics are full with God’s value that is implemented in honesty value and this is one of the charasterics of madura people in their daily life. The holistic concept will be very important in this research as the foundation that will be internally fused in the building of the holisctic Indonesian Accountant Code of Ethics with the Ghai’ Bintang song. The Holistic approach is a way in a research in building new concept from the previous one. This research has produced the holisctic Indonesian Accountant Code of Ethics in which based on the values of knowledge principles, competence, defenselesness, grateful, and happiness. Those five principles must be covered with hinesty value as the spearhead of moral that has to be owned by each accountant. Those principles are part of the transformation of God Values that must be applied by every human being in the earth. Thus, this is also a responsibility for each accountant when they take action in their professional activities. Moreover, the implementation of Madura local culture ethical value may become a new foundation of the reformation of accounting profession’s code of ethics in Indonesia in this industry revolution era.